Keterampilan Membuka dan Menutup Pelajaran Mahasiswa Calon Guru IPA dalam Pelaksanaan Praktik Mengajar - Fitriyah, Lina Arifah; Hayati, Nur; Af’idah, Noer; Manasikana, Oktaffi Arinna (Jurnal Simki Pedagogia, 2024)
This research aims to describe the skills of opening and closing lessons when prospective science teacher students practice teaching. This experiment is included in single subject research which is analyzed descriptively-quantitatively for students who will become science teachers and take microteaching courses. A teaching skills assessment rubric was used to obtain data for this research. The results of the study show that 1) the skill of opening lessons for prospective science teacher students is in the good category for each activity, namely the lesson begins with greetings then prepares students to learn, conducts apperception and explores students' initial knowledge, and communicates learning objectives. 2) skills in closing science teacher candidate students' lessons in a good category in reflecting and concluding learning material, giving follow-up directions regarding assignments or learning material for the next meeting, and ending the lesson by giving greetings and the like.